Corona Virus, China-US Rivalry and Its Implications to Indonesia: A Preliminary Note - Al Chaidar; Herdi Sahrasad; Dedy Tabrani; Ti Aisyah; Muhammad Ridwan (Budapest International Research and Critics University, 2022)
This article explains that in the midst of the widespread Corona Virus (Covid-19) outbreak, the United States accuses China of being the ringleader of the Corona spreader, and on the contrary China blames the US for making corona. The controversy about who is the spreader of the Corona pandemic, instead led to mutual suspicion between the US vs. China, while it did not solve the Corona outbreak problem that threatens the world community. Today, for the peoples in various parts of the world today, the main problem for overcoming Corona is the inability of the state to deal with the deadly virus. So that cooperation and mutual trust between nations will enable us all to overcome Corona outbreaks. Noah Harari's view should not be forgotten that the experience of the world community in eradicating the 2014 Ebola outbreak teaches us that closer, open and mutual trust in global cooperation will not only be a victory for humanity over the Corona virus, but also a victory against all pathogenic viruses in the future.